Removal of ni(II) from aqueous solutions by sorption - Sharma Y.C.; Prasad G.; Rupainwar D.C. (My University, 2025)
Adsorption of Ni(II) from its aqueous solutions on China clay, a cheap clay mineral, has been found quite favourable; a maximum removal of 75.3% was obtained at 50 mg L-1 metal concentration and a pH of 6.5 at 30°C. Dynamic modelling of the nickel uptake has been worked out and found to be of the first order. The rate constant was found to be 9.21 x 10_1min-1 under the above optimum conditions of the experiment. Coefficients of the mass transfer and intraparticle diffusion were also evaluated and found to be 2.8 x 10-2cm s-1and 4.50 x 10-2cm2 s-1 respectively. Langmuir’s model was used for the equilibrium modelling and the constants were calculated at 30, 40 and 50°C. Thermodynamic study at different temperatures was undertaken and the values of change in the standard free energy (ΔG°), enthalpy (ΔH0) and entropy (ΔS°) are reported. Low temperature and high pH favour the removal of nickel (II) by adsorption on China clay. © 1991, Taylor & Francis Group, LLC. All rights reserved.